Anthropometrics Analysis of Mental Foramen and Accessory Mental Foramen in Zambian Adult Human Mandibles - Balakrishnan Subramanian; Severine N. Anthony; Lumamba Mubbunu; Chitinti Hachombwa; Majuto S. Mlawa; Mudhihiri M. Majambo; Rajab M. Sasi (The Scientific World Journal)
The mental foramen (MF) and accessory mental foramen (AMF) are the strategically important landmarks during surgical interventions and anaesthetic nerve blocks procedures involving the mental nerve. The study aimed at evaluating anthropometrics of MF and AMF in Zambian adult human mandibles and it was cleared for ethics from TDRC Ethics Review Committee (Reg. No.: 00002911; FWA: 00003729). A total of 33 Zambian adult human mandibles were evaluated for shape, position, and direction of opening of foramen. All measurements were performed using a Digital Vernier Calliper and statistically analysed for per cent frequency and mean and standard deviations, and we performed the one sample t-test for comparative analysis. Data were considered significant at p<0.05. All mandibles that were examined had bilateral MF while unilateral AMF was found in two mandibles (6%). The foramens were mostly oval in shape and their most common position was between the second premolar and first molar and the most common orientation was posterior-superior. The comparative analysis of mandibular anthropometrics showed significant variations (p<0.05) with different ethnic groups. The findings emphasize the ethnic variations and edify that the foramen position is not always as stated in reference textbooks. The clinical creditability of the study is cautioning the surgeons on possible variations of the MF and AMF anthropometrics compared to existing literature in order to avoid any unforeseen injury related to anaesthesia or dental surgeries. Further studies with large sample sizes representing whole country are recommended to establish the standard MF and AMF anthropometrics of Zambian population.